2003
DOI: 10.1016/s0885-3924(03)00056-3
|View full text |Cite
|
Sign up to set email alerts
|

Maximizing Benefits and Minimizing Risks in Palliative Care Research That Involves Patients Near the End of Life

Abstract: Research in end-of-life care is constrained more by pragmatic, social, cultural, and financial constraints than ethical issues that preclude the application of typical research methodologies. When normally accepted and ethically sound protections for subjects (especially for those who lack independent decision-making) are in place, exclusion of patients with far advanced disease from research is in and of itself unethical. Involvement in research may have a therapeutic, anticomiogenic effect on dying patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 14 publications
0
46
0
Order By: Relevance
“…Dementia patients have cognitive impairment so usually only proxies can give consent for the patient's participation. There are also the practical challenges of poor recruitment and limited follow-up [133,134]. Further, the frailty trajectory of decline results in difficult prognostication with the result that dementia may not be recognized as a terminal condition making it difficult to define an end-of-life population.…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%
“…Dementia patients have cognitive impairment so usually only proxies can give consent for the patient's participation. There are also the practical challenges of poor recruitment and limited follow-up [133,134]. Further, the frailty trajectory of decline results in difficult prognostication with the result that dementia may not be recognized as a terminal condition making it difficult to define an end-of-life population.…”
Section: Research Trends In Dementia At the End Of Lifementioning
confidence: 99%
“…However, on the other side of the debate, there is growing literature that argues that a marked exclusion of people at end-of-life from research may also be unethical (Fine, 2003). In addition, there is evidence that people at end-of-life want to be involved as participants in research, or at least given the choice as to whether to be involved or not (Addington-Hall, 2002;Tuffrey-Wijne, Bernal, & Hollins, 2008).…”
Section: Terminally Ill Individuals As Vulnerablementioning
confidence: 99%
“…Other potential benefits of participation identified in the literature include the potential therapeutic effects that research can have on dying persons and their families by eliciting feelings of purpose and meaning, and other perceived benefits such as companionship and the validation of being able to engage in a meaningful activity (Fine, 2003;Terry et al, 2006;Tuffrey-Wijne et al, 2008). The terminally ill participants in the study by further reported that they preferred qualitative research methods, stating that they felt "these methods allow people to raise and contextualise issues important to them" (p. 3).…”
Section: Terminally Ill Individuals As Vulnerablementioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] Research that focuses on end-of-life issues is often considered too burdensome, potentially distressing, or harmful to terminally ill patients. 10 Because of the perceived vulnerability of palliative care patients, hospital Institutional Review Boards (IRBs) may be reluctant to permit psychosocial research, for fear that there are minimal benefits and even the potential for harm.10,11 These concerns are even more pronounced when research focuses specifically on topics related to death and dying.…”
Section: Introductionmentioning
confidence: 99%